Experimental Study of Electrode Variation Effect on Connection Strength for Underwater Welding - Nur Syahroni; Yeyes Mulyadi; Benedictus Arif Wicaksono (International Journal of Offshore and Coastal Engineering, 2022)
SMAW welding has various electrodes that can be used in underwater welding. This study will analyze the influence of electrode type on mechanical properties and the influence ofwelding position on the mechanical properties of joints for underwater welding. This experiment results show that the E7016 electrode pull test has a superior value than the E6013 and E7018 electrodes; when compared between E6013 and E7016, it is reasonable if the E7016 is stronger than E6013 and the frequency level is higher than E6013 even if it already uses a different amper. However, if the E7016 electrode compared to the E7018 is still superior to the E7016 electrode using the same voltage and amper. In addition, the results of macro test observations show that welding using the E7018 electrode has lower porosity levels than E7016 electrodes, while with the same experiment results, the tensile strength of the E7016 is superior to the E7018. So that the power value of E7016 electrodes can be superior to E7018 in this experiment is not only based on porosity that occurs but also slag and imperfect penetration also determines the strength of welding results by using E7016 electrodes.